4E analysis and multi-objective optimization of a micro poly-generation system based on SOFC/MGT/MED and organic steam ejector refrigerator. (1st September 2020) - You, Huailiang; Han, Jitian; Liu, Yang; Chen, Changnian; Ge, Yi
Abstract: This paper presents 4E (energy, exergy, economic and environmental) analysis and multi-objective optimization of a micro poly-generation system to produce power, cooling, heating and freshwater, which consists of solid oxide fuel cell (SOFC), micro gas turbine (MGT), multi-effect desalination (MED) unit, organic steam ejector refrigerator (OSER) and heat exchanger. The mathematical model is developed, and system performance under the design condition is evaluated. The effects of system parameters such as fuel utilization factor, air to fuel ratio, feed seawater temperature, evaporating pressure in generator and OSER entrainment ratio on 4E performance are analyzed. Two groups of multi-objective optimizations using NSGA-Ⅱ method are conducted to achieve the optimal system performances in three typical scenarios. The analysis results show that the proposed system can provide power, cooling, heating and freshwater at loads of 295.4 kW, 14.33 kW, 8.096 kW and 0.1303 kg/s with the total cost being 11.63 $/h under the design condition, and the system electrical, exergy, and overall energy efficiencies are 62.40%, 64.70% and 67.13%, respectively. It is also indicated that the optimal overall energy efficiency of system is found to be 71.24% in the first group of optimization which is 4.11% higher than that under the design condition. Highlights: A novel micro poly-generation system based on SOFC/MGT/MED is proposed. 4E (energy, exergy, economic, and environmental) analysis is performed. Multi-objective optimization considering five objectives is conducted by NSGA-Ⅱ. The optimal overall energy efficiency is 4.11% higher than the design condition.